Fast-wood forestry: myths and realities [Japanese] - Cossalter, C.; Pye-Smith, Charlie (Center for International Forestry Research, 2005)
This book provides a comprehensive analysis of the arguments for and against fast-wood platations. It separates fact from fiction, science from speculation, truth from misinformation. Environmentalists have frequently exaggerated the malign impact of fast-wood plantations. At the same time plantation companies have underestimated the damage that fast-wood forestry has done, both to the environment and local communities. This book explores in detail the impact of the industry on biodiversity, soil and water resources. It analyses the claims made by plantation companies that fast-wood forestry brings valuable social benefits jobs, infrastructure and wealth--to rural communities. And it assesses the merits--or otherwise--of the subsidies and incentives used by governments and international agencies to encourage the industry. It conludes with a series of recommendations that suggest how the industry could improve its environmental and social performance.